2011
DOI: 10.1104/pp.111.175950
|View full text |Cite
|
Sign up to set email alerts
|

ABI4 Activates DGAT1 Expression in Arabidopsis Seedlings during Nitrogen Deficiency      

Abstract: Triacylglycerol (TAG) is the major seed storage lipid and is important for biofuel and other renewable chemical uses. Acylcoenzyme A:diacylglycerol acyltransferase1 (DGAT1) is the rate-limiting enzyme in the TAG biosynthesis pathway, but the mechanism of its regulation is unknown. Here, we show that TAG accumulation in Arabidopsis (Arabidopsis thaliana) seedlings increased significantly during nitrogen deprivation (0.1 mM nitrogen) with concomitant induction of genes involved in TAG biosynthesis and accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 59 publications
(60 reference statements)
4
99
0
1
Order By: Relevance
“…Consistent with this, lateral root formation in abi4 is no longer affected by exogenous cytokinin. ABI4 appears to be also required for lipid biosynthesis in seedlings during nitrogen deficiency (Yang et al, 2011). In our study here, we showed that ABI4 plays an important role in regulating root growth.…”
Section: Abi4 Regulates Root Growth In a Dosage-dependent Mannersupporting
confidence: 64%
“…Consistent with this, lateral root formation in abi4 is no longer affected by exogenous cytokinin. ABI4 appears to be also required for lipid biosynthesis in seedlings during nitrogen deficiency (Yang et al, 2011). In our study here, we showed that ABI4 plays an important role in regulating root growth.…”
Section: Abi4 Regulates Root Growth In a Dosage-dependent Mannersupporting
confidence: 64%
“…Among 113 potential triacylglycerol biosynthesis genes, 10 had putative loss-of-function frameshifts due to large-effect SNP and/or indels, including the DGAT homolog (Glyma16g21960, GmDGAT2B) and a homolog of Abscisic Acid Insensitive 4 (ABI4) (Glyma14g06290), a transcription factor that regulates triacylglycerol synthesis in Arabidopsis by activating DGAT1 expression during nitrogen deficiency (Supplementary Fig. 21) 39 . A frame-shift mutation in GmDGAT2B was previously found to be associated with reduced seed oil concentration 40 .…”
Section: Npgmentioning
confidence: 99%
“…During nitrogen deficiency, ABI4 (abscisic acid insensitive4), an AP2 (activator protein-2) type transcription factor, activated the expression of the DGAT1 (acyl-coenzyme A:diacyglycerol acytransferase 1) gene, which is the rate-limiting enzyme in triacylglycerol biosynthesis. ABI4 binds the CE1-like cis element (CACCG) on the DGAT1 promoter that leads to an acceleration of triacylglycerol accumulation in nitrogen limited plants (Yang et al 2011).…”
Section: Nitrogenmentioning
confidence: 99%